Analisis Tiktok terhadap Pengambilan Keputusan Memilih Gen Z dalam Pilpres di Salatiga - Irvanius, Rizki; Sari, Dewi Kartika; Suparno, Antonius (Innovative: Journal Of Social Science Research, 2025)
The 2024 Presidential dan Vice Presidential Elections yesterday were very interesting with various strategies prepared to win the election. This study analyses the influence of Tiktok on the decision to elect the President and Vice president among Generation Z in the 2024 presidential election in Salatiga City. With increasing technological advances and increasing internet usage, Generation Z is as importan group in the presidential election, utilising Tiktok to obtain political information. This research aim at how Tiktok can influence the decision to vote for President and Vice President among Generation Z. Using descriptive quantitative method conducted throufh questionnaires distributed randomly to Generation Z in Salatiga. the findings of this study indicate that Tiktk can have an impact and a significant influence on voting interest for Generation Z in Salatiga City.